Pemilahan Sampah Pada Kedai Kopi di Lingkar Kampus USK Menuju Eco Living Coffee Shop - Nursaniah, Cut; Suhaeri, Suhaeri; Malahayati, Nurul; Hasibun, Muammar; Abrar, Syahrul; Anoora, Rana; Nurisra, Nurisra; Riyaldi, Muhammad Haris; Afani, Rayyan Jura (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2025)
Coffee is one of the main commodities in Aceh and its existence encourages the growth of coffee shop businesses, including around the Syiah Kuala University (USK) campus. Unfortunately, most coffee shops have not implemented environmentally friendly principles, especially in waste management. This community service activity aims to implement appropriate technology (TTG) in waste management at the Zakir Coffee Shop (Partner 1) and Aceh House Kupi (Partner 2) through collaboration with the USK Waste Bank Unit (BSU) (Partner 3). Activities include waste sorting training, making compost from coffee waste, and. This waste sorting is the first step towards the eco living coffee shop concept. TTG for waste management has been given to partners 1 and 2 in the form of sorting containers, waste management management from transportation, processing coffee waste into compost, processing inorganic waste into useful products and education on the eco living coffee shop concept and producing a map of coffee shops around the campus in waste sorting which is the HKI Copyright Map. This activity also involves Thematic KKN students. The involvement of Thematic KKN students who are actively involved in this activity. The results of the activity show an increase in awareness of shop managers and the creation of a zero waste system that can be replicated in other locations.